He iwi ke koutou, he iwi ke matou, engari i tenei wa, tatou, tatou e = You are different, we are different, but we are able to work together : Family Partnership as a model for cultural responsiveness in a Well Child context : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Nursing at Massey University, Albany, New Zealand - Tipa, Zoe Kristen (Massey University, 2013)
In 2006 the Royal New Zealand Plunket Society embraced a model of communication and practice titled Family Partnership. The Family Partnership model and training is designed to develop the communication skills of professionals working with families in order to acknowledge and enhance the capabilities of parents. It is acknowledged that the degree to which a service is culturally safe is defined by the individual receiving the service. Nurse leaders, educators and peers are consistently required to make judgements as to the extent to which the nurse being observed is culturally safe, without obtaining client feedback. This research examined whether the Family Partnership model could be considered a model for cultural responsiveness with the dual benefit of providing a platform to more accurately assess the cultural competence of Plunket nurse practice. An evaluation design and methodology was used to determine the relationship between Family Partnership training for Plunket nurses in relation to Māori health outcomes. There were two phases in the data collection process. In phase one an online survey was completed by a group of Plunket nurses who had completed Family Partnership training along with a group that had not completed Family Partnership training. Phase two included ten observations and interviews with Plunket nurses and Plunket clients who identified as Māori. A combination of evaluation tables to determine merit and thematic analysis were used for the analysis of the mixed methods data. The results were presented in three sections relating to Plunket nurse practice, client experience and the impact on Plunket as an organisation. All Plunket nurses who participated in the research believed that Family Partnership had a positive impact on their clinical practice. The extent to which their practice had changed was difficult to determine, however the need for ongoing updates in Family Partnership was strongly indicated. Māori Plunket clients were generally satisfied with the Plunket service and their responses aligned with the concepts outlined in Family Partnership communication theory. The relationship between the findings and the principles of the Treaty of Waitangi were highlighted. This research has indicated that cultural responsiveness can be defined as the way in which a service identifies and attempts to meet the needs of the individual. It has discussed the complexity around what constitutes a health outcome for Māori clients and ultimately how cultural competence may be better assessed in practice.
Keywords: Royal New Zealand Plunket Society; Maori community nursing; Well Child; Family Partnership; Cross-cultural nursing; Cultural awareness; Whanau ora; Tamariki ora; Infant health services; Family services